Communication and Kinship.On “Koin?nia” and “Syngeneia” in Plato’s Dialogues - Delle Donne, Carlo (2022)
The purpose of this paper is to shed light on the multiple functions of the notion of koin?nia in Plato’s dialogues. Koin?nia and its absence characterize reality as a whole: both the intelligible and the sensible entities either “communicate” or do not “communicate” (koin?nein); therefore, reconstructing the net of koin?nia-relationships amounts to putting dialectics into practice. So far so good. But an analysis which aims at clarifying the role played by koin?nia cannot but take also syngeneia into account. The reason for this fact lies in the essential link which binds koin?nia and syngeneia, with the latter being the condition of possibility of the former.